ความต้องการล่ามในตลาดแรงงานไทย: การศึกษาประกาศรับสมัครงานออนไลน์ - พูลลาภ, ทองทิพย์ (Journal of Letters, 2016)
บทความนี้มีวัตถุประสงค์เพื่อศึกษาความต้องการล่ามในตลาดแรงงานไทย เพื่อให้ทราบว่าผู้ว่าจ้างต้องการล่ามภาษาใด ในบริบทใด และผู้สมัครควรมีคุณสมบัติใดบ้าง ผู้วิจัยเก็บข้อมูลจากประกาศรับสมัครล่ามจำนวน 260 ประกาศจากเว็บไซต์สมัครงาน 6 แห่งตั้งแต่วันที่ 1 ตุลาคม–31 ธันวาคม 2558 จากนั้นจึงวิเคราะห์เนื้อหาข้อมูลและลงรหัสในโปรแกรม Microsoft Excel ผลการวิจัยพบว่า ภาษาที่ผู้ประกอบการต้องการล่ามมากที่สุดคือภาษาญี่ปุ่น (ร้อยละ 70) รองลงมาคือภาษาจีน (ร้อยละ 20.38) ตามด้วยภาษาอังกฤษ ภาษาพม่า ภาษาเกาหลี ประกาศร้อยละ 96.54 รับสมัครล่ามในตำแหน่งพนักงานประจำ โดยพบว่ามีความต้องการในภาคการผลิตมากที่สุด ผู้ว่าจ้างส่วนใหญ่ต้องการล่ามวุฒิการศึกษาปริญญาตรีสาขาภาษาหรือสาขาที่เกี่ยวข้อง ล่ามที่ผู้ว่าจ้างต้องการควรจะเป็นผู้มีทักษะทางภาษาดี มีทักษะการแปลและการล่าม ทักษะความสัมพันธ์ระหว่างบุคคล และทักษะการทำงานเป็นทีม นอกจากนี้ยังต้องมีบุคลิกดี มีใจรักการบริการ และทำงานภายใต้ความกดดันได้ ผลการวิจัยชี้ให้เห็นว่าควรมีการจัดการเรียนการสอนล่ามให้กับนิสิตนักศึกษาระดับปริญญาตรี เพื่อเตรียมความพร้อมก่อนเข้าสู่ตลาดแรงงานและเพื่อเป็นการตอบสนองความต้องการล่ามของภาคธุรกิจ Investigating the Needs for Interpreters in the Thai Labor Market through Online Job Advertisements This research aims to explore the needs for interpreters in the Thai labor market in a bid to identify the languages and the settings in which interpreters are required as well as their preferred qualifications. To this end, 260 job advertisements for interpreters were collected from 6 recruitment websites between 1 October and 31 December 2015. Content analysis was performed on the data, which was codified in the Microsoft Excel for quantitative analysis. The areas investigated included the languages required, settings, qualifications (nationality, sex, age, education, skills and personal attributes, standardized proficiency tests, experience), and the types of employment, geographical locations, and salary. It was found that the languages most needed were Japanese (70%) and Chinese (20.38%), followed by English, Burmese, and Korean respectively. 96.54% of the ads sought in-house interpreters, who were needed most in the manufacturing industry. Most ads listed Bachelor’s degree in language or related fields, and successful candidates were required to possess strong language skills, translation and interpreting skills, interpersonal skills, and teamwork skills, as well as a good personality, service-mindedness, and the ability to work under pressure. The findings suggested that interpreting should be taught to undergraduates to prepare them for the labor market and to respond to the needs of the business sector.